THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON THE FIRM VALUE OF PROPERTY & REAL ESTATE - Cahyono, Tyas Dwi (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
This study aims to examine The Influence of Good Coporate Governance and Corporate Social Responsibility on firm value. The population used is Property & Real Estate companies listed on the Indonesia Stock Exchange in 2020-2022 with a total sample of 54 companies using puposive sampling technique. Data analysis using multiple regression analysis. The results showed that corporate social responsibility has a positive effect on firm value, the independent board of commissioners has a negative effect on firm value, and managerial ownership, institutional ownership has no effect on firm value.